Path visualization: a method for objective measurement of spatial visualization. Issue 4 (2nd October 2019) - Lyon, Don R.; Gunzelmann, Glenn; Krusmark, Michael
ABSTRACT: The ability to mentally represent spatial information is a fundamental cognitive process. To many people, this process feels a bit like visual perception, hence the term 'spatial visualization'. In this paper, we describe a method for measuring the accuracy of spatial visualization, specifically visualization of a complex path in imaginary space. A critical feature of this method (called Path Visualization) is that it relies on the detection of intersections in a visualized path. Intersection detection is an inherently spatial task that requires a spatial representation. In this paper, we show how the Path Visualization method works, and how it can be customized to address several key research issues in human spatial cognition.